Understanding the Complexity of Investment Behavior: A Qualitative Study - Sholika, Shinta Anatus; Zaki, Achmad (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Financial literacy also influences an individual's perception of investment risk. Individuals with high levels of financial literacy tend to understand better the risks associated with various types of investments and can manage these risks effectively. This research aims to determine how individuals' financial literacy levels influence investment decisions, understand the relationship between individual financial behavior and the investment decisions they make, and ascertain how financial literacy contributes to the formation of more disciplined and planned investment behavior. The method used in this research is the descriptive qualitative method. The findings of this research indicate that efforts to improve financial literacy in society must be accompanied by a holistic approach that considers various aspects influencing individual investment behavior.